Pengaruh Pertemanan Sebaya terhadap Prestasi Belajar Pendidikan Agama Islam Siswa Kelas XI SMA Negeri 1 Sewon, Bantul Tahun Pelajaran 2013/2014 - Mujiastuti, Agustina Ika Candra; Ilyasir, Fiska (Literasi: Jurnal Ilmu Pendidikan, 2015)
Abstract Agustina Ika Candra Mujiastuti: The Effect of Peer Friendship Among Grade XI Students at SMA Negeri 1 Sewon, Bantul in academic year 2013/2014. Undergraduate Thesis. Yogyakarta: Islamic Education Studies Program, Alma Ata School of Islamic Studies, 2014. This study was conducted to determine the level of peer friendships among Grade XI Students of SMA Negeri 1 Sewon, Bantul for academic year 2013/2014 and its effects on learning achievement of Islamic Religious Subject. This correlational study was using quantitative approach. Using random sampling techniques, the sample of this study were 69 of 273 Grade XI students at SMA Negeri 1 Sewon Bantul Academic Year 2013/2014. Data collected by observation, questionnaires, interviews, and documentation. Data analysis techniques used include descriptive and inferential analysis using Product Moment Correlation with SPSS version 16.0. The results showed: 1) The level of peer friendship among students garde XI at SMA Negeri 1 Sewon, Bantul was in intemediate category, with the percentage of 37.7%. 2) The learning achievement of the students for Islamic Religion Seubject was in intermediate category with the percentage of 17.4%. 3) There was a significant effect of peer friendships on learning achievement of Islamic Religion Subject among Grade XI student of SMA Negeri 1 Sewon, Bantul in the school year 2013/2014, for the value of r count> rt, namely 0.639> 0232 at a significance level of 5% and 0.639> 0302 at the level of 1%, with strong category. Keyword: effects, friend, achievement